2022
DOI: 10.1021/acs.orglett.2c04050
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Mediated Conjugate Addition of Isocyanides to β-Hydroxy-α-diazo Carbonyls: Synthesis of β-Carboxamido-α-diazo Carbonyl Compounds

Abstract: A Lewis acid mediated conjugate addition of isocyanides to β-hydroxy-α-diazo carbonyls has been developed for the first time. The reaction realizes the efficient construction of quaternary carbon centers and provides a novel and efficient strategy for the synthesis of β-carboxamido-α-diazo carbonyls that would be otherwise difficult to form in a single step. Further applications, including synthesis of methylenecyclohexane, spiro-β-lactam, and nitrogen-bridged tricyclic β-lactam, demonstrated the tremendous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Therefore, development of visible-light-induced 6- endo-trig radical cyclization of o -alkenyl aromatic isocyanides, especially for the radical cyclization of o -alkenyl aromatic isocyanides with thioethers, is a highly desirable, yet challenging goal. As a continuation of our studies on the applications of isocyanides 14 and visible-light-induced radical reactions, 15 herein we report a novel visible-light-induced radical cyclization of o -alkenyl aromatic isocyanides with thioethers for the first time (Scheme 1(d)). This reaction offers a new and efficient strategy for the synthesis of highly functionalized 2-thioquinolines in a single step.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, development of visible-light-induced 6- endo-trig radical cyclization of o -alkenyl aromatic isocyanides, especially for the radical cyclization of o -alkenyl aromatic isocyanides with thioethers, is a highly desirable, yet challenging goal. As a continuation of our studies on the applications of isocyanides 14 and visible-light-induced radical reactions, 15 herein we report a novel visible-light-induced radical cyclization of o -alkenyl aromatic isocyanides with thioethers for the first time (Scheme 1(d)). This reaction offers a new and efficient strategy for the synthesis of highly functionalized 2-thioquinolines in a single step.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, development of a general and metal-free method to access pyrroles via a visiblelight-induced [3+2] annulation of vinyl azides and diverse alkenes with broad functional group tolerance is highly desirable, yet a challenging goal. As a continuation of our studies on the synthesis of nitrogen-containing compounds, [14] herein, we report a visiblelight-induced [3+2] annulation of alkenes with vinyl azides in the presence of organic dye photocatalysts without other additives. The reaction works with a broad range of polarized olefins, and provides a simple and novel method for the synthesis of polysubstituted pyrroles in a single step (Scheme 1, b).…”
Section: Background and Originality Contentmentioning
confidence: 90%
“…The evaluation of solvents revealed that DCM seemed to be the best choice. Other solvents tested, such as DCE, MeCN and toluene, gave lower product yields (entries [12][13][14]. When the reaction was carried out at 40 °C under otherwise identical conditions, the product 3aa was produced in 58% yield (entry 15).…”
Section: Phmentioning
confidence: 99%